Dynamics of the interaction between adults and a preschool child with autism: Transition from segregated to inclusive settings - André, Amael; Despois, Julien; Amiot, Leslie; Deneuve, Pascale (Frontiers in Education, 2022)
This study explores the dynamics of the interaction between the engagement of a preschool child with autism spectrum disorder and the participation of adults, notably during the child’s transition from a segregated to inclusive setting. Nine classroom sessions were filmed over an 8-month period with a focus on two types of activities: free play and adult-led gross motor activities. Our results showed that the interactions evolved differently over time for the two activities. During gross motor activities, the active engagement of the child associated with the passive participation of adults, which increased in the segregated setting, continued to develop in the inclusive setting leading to the emergence of active engagement with peers at the end of the school year. During free-play, the child engagement progressed in the segregated setting. Though initially in a state of passive observation, the child became independently active, either with or without the guidance of adults. The transition from the segregated setting to the inclusive setting without adult participation leads to a momentary drop in the child’s active engagement before the reemergence of independent active engagement. The results of this study question the methods used and the resources invested in preschools to favor the inclusion of young children with autism. They highlight the importance of adults’ participation during the transition between segregated and inclusive settings. In addition, they encourage adults to accept the temporary regression in child engagement in order to attain desirable outcomes such as independent engagement at a later time.